System Programming Drawbacks - Jain, Abhishek; Kumar, Manohar; Kumar, Manohar (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
A system programming language usually refers to a programming language used for system programming; such languages are designed for writing system software, which usually requires different development approaches when compared to application software. System software is computer software designed to operate and control the computer hardware, and to provide a platform for running application software. System software includes software categories such as operating systems, utility software, device drivers, compilers, and linkers. In contrast with application languages, system programming languages typically offer more-direct access to the physical hardware of the machine: an archetypical system programming language in this sense was BCPL. System programming languages often lack built in input/output facilities because a system-software project usually develops its own input/output or builds on basic monitor I/O or screen management services facilities. The distinction between languages for system programming and applications programming became blurred with widespread popularity of PL/I, C and Pascal.